TRANSFORMASI LINTAS GENRE: DARI NOVEL KE FILM, DARI FILM KE NOVEL - Heru S. P. Saputra (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2009)
This article is aimed at scrutinizing the ecranisation in thetransformation across genre, that is from novels to films, and viceversa. It was found that the ecranisation process from novels tofilms is a process envolving the reactualisation from the writtenlanguage to the audio visual language. The implication of thatprocess is that there are some efforts to shrink, add, or alter partsof the story for various goals. Seen from the perspective of thesociology of literature, this effort could initiate the low readingmotivation to the high watching motivation. In the context ofaesthetic idealism, ecranisation actually exposes an author’sdepression due to his lack of ability to articulate his audio visuallanguage in representing the written language. In contrast, filmshas been de-ecranised into novels. An across genre transformationprocess is thus made, that is from the audio visual tradition,wrapped by advanced technology, to the reading-writing tradition.The latter tradition phenomena is different from the former,specifically in its perspective of the social function of literature.Unfortunately, both cannot avoid the hegemony of industrialisation.Literature and films are no more concerned with easthetic values.Rather they mingle in industrialisation, in particular theentertainment industry.